Thirdhand Smoke Beliefs of Parents - Odacı, Nurbanu; Kitiş, Yeter (Addicta: The Turkish Journal on Addictions, 2025)
Parents are responsible for protecting their children from the harmful effects of thirdhand smoke (THS). The purpose of this descriptive study was to examine parents’ beliefs about third-hand smoke. Data were collected using the “Introductory Information Form” and the “Turkish Version of the Beliefs About Third Hand Smoke Scale.” The sample consisted of 895 parents living in Ankara. Data were analyzed using Mann–Whitney U and Kruskal–Wallis-H tests. Eighty-two percent of the participants did not know the concept of THS. The mean scale score of the participants was 4.01 ± 0.82. Scale score means were higher for participants who banned smoking in their homes and cars (p < .05). The results show that most parents do not know the concept of THS. Parents’ awareness should be increased to protect children from THS exposure.
Keywords: Parents; smoke; smoke-free policy